Multi-omics integration uncovers key transcriptional regulators in triple-negative breast cancer spatial heterogeneity - Zhang, Ning; Zhang, Ye; Yang, Rui-Fei; Tan, Min; Chu, Hai-Qing; Rehman, Abdur; Yang, Lu-Yu; Li, Ya-Yu; Alshabrmi, Fahad M.; Zhou, Xin; Xu, Feili; Gong, Shou-Ping; et al. (Frontiers in Genetics, 2025)
BackgroundTriple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer characterized by a lack of hormone receptors, making it challenging to treat.MethodsWe generated a comprehensive spatial cell atlas of TNBC using a multi-omics integration approach that combined single-cell RNA sequencing (scRNA-seq) with spatial transcriptomics. This integration allowed us to characterize the spatial microenvironment and map the cell-type-specific distributions in TNBC tissues.ResultsOur analysis revealed significant heterogeneity in cell types and spatial distribution, with normal regions enriched in insulin resistance functions, whereas cancerous regions displayed diverse cell populations, including immune cells, cancer-associated fibroblasts (CAFs), and mesenchymal cells. By constructing transcription factor (TF) regulatory networks, we identified TFF3, RARG, GRHL1, RORC, and KLF5 as critical regulators of epithelial cells, whereas EMX2, TWIST1, TWIST2, NFATC4, and HOXC6 were found to play essential roles in mesenchymal cells. Immunohistochemical validation supported the involvement of these TFs in TNBC. Further analysis of receptor-ligand interactions highlighted the roles of KNG1_BDKRB2 and NRG1_ERBB4 signaling in promoting tumor aggression, suggesting potential therapeutic targets. GO enrichment analysis revealed overlapping pathways between epithelial and mesenchymal cells, focusing on migration, signaling, and development, indicating that the shared regulatory mechanisms contribute to cancer progression.ConclusionOur findings provide new insights into the TNBC microenvironment, emphasizing the complex spatial interactions between different cell types and highlighting key regulatory pathways that could be targeted for future therapeutic interventions. This spatial cell atlas lays the foundation for further exploration of tumor microenvironment dynamics and precision oncology approaches.